Experimental Study on Moisture Migration in Unsaturated Sand Under Cyclic Diurnal Temperature Variation - Mao, Xuesong; Zhang, Jianxun; Wu, Qian; Liu, Feifei; Li, Xiangyu; Wang, Yueyue (Frontiers in Earth Science, 2022)
The phenomenon of mixed migration of liquid water and water vapor appeared in subgrade covered with an impermeable semi-arid rigid base. The soil-water characteristic curves (SWCC) at different temperatures are a key factor in revealing the mechanism of liquid water migration. In particular, the matric suction of unsaturated soil is considerably affected by the change in temperature. A moisture migration laboratory experiment can visually observe the moisture migration process. Therefore, matric suction tests with different temperatures and moisture migration of the one-dimensional soil column were conducted. Then the non-isothermal SWCC model was extended based on the Van Genuchten (VG) model, and the validity was given. Based on the above results, the mechanism of the mixed migration of liquid water and water vapor in moisture migration of unsaturated soil under the effect of the cyclic diurnal temperature variation was revealed. The research demonstrated that the matric suction of unsaturated sand decreases with the increase in temperature. During the daytime, the temperature of the soil column gradually increases. Except for a part of liquid water transformed into water vapor, the liquid water migrated downward under the action of gravity and matric potential. At night, the water vapor accumulated beneath the lid condensed into liquid water under the action of the temperature sharply decreased, which was the main reason for the moisture aggregate beneath the closed layer. Meanwhile, the liquid water and water vapor mutually transformed and dynamically migrated in the soil column under the effect of the cyclic diurnal temperature variation. The moisture in the soil column dynamically migrates between daytime and night, which is named the “moisture circulation of covering effect” in this paper. The “moisture circulation of covering effect” would progressively attain a dynamic equilibrium and dynamic circulatory between the daytime and night with time.